International Boarding School with an Eco-technology Architecture Approach in South Jakarta - Rafi Hafuza; Moch Fathoni Setiawan; Didik Nopianto Agung Nugradi; Eko Budi Santoso (Universitas Negeri Semarang, 2024)
Educational innovation is an important factor for educational progress. Unfortunately, the implementation of educational innovation in Indonesia has not run smoothly as expected. This situation requires systemic reformulation by taking into account various factors such as political, economic, social and cultural factors. Judging from the importance of education, the combination of international schools and boarding schools is the right innovation choice in the current era. International Boarding Schools can be a way to create a generation that is advanced, independent, responsible and able to compete in developing science, technology and skills at an international level. By using an international curriculum and combining it with a boarding system in learning practices, it is hoped that the Indonesian generation can achieve a generation that is intelligent, independent and broad-minded. Not only about the educational aspect, International Boarding Schools can also be a solution to overcome traffic jam problems that occur, especially in big cities. With the Boarding system, parents no longer have to pick up and pick up their children to study at school, thereby reducing the quantity of motorized vehicles on the road. The construction of facilities in a city does not always go well and produce good results, many facilities are built which make the quality of the environment worse. Therefore, to reduce negative impacts on the environment, facilities to be built should apply an environmentally friendly design approach to reduce damage to the environment around the building in the short and long term. The international boarding school is planned on a site of 1,154 ha, on Letnan Jendral Soepeno Street, Kebayoran Lama, South Jakarta, Special Capital Region of Jakarta. The facilities at the school include classrooms, laboratories, dormitories and other supporting facilities that follow international school standards.